PRONUNCIATION ERRORS IN SPEAKING PERFORMANCE OF GRADE 11 STUDENTS AT SMA NEGERI 20 MEDAN - Alifah Hidayati and Anni Holila Pulungan (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2018)
In the process of learning English as a foreign language, many students make errors in pronouncing English words. This study aimed to identify kinds of pronunciation errors, specifically pronunciation errors on consonant and vowel sounds. And to find out the causes of error in English pronunciation of grade 11 students at SMA Negeri 20 Medan. The research was conducted by descriptive qualitative methods. In collecting data, firstly recording the pronunciation of students’ speaking performance. Then, transcribing their utterances which contains consonant and vowel sounds. Furthermore, the data are analyzed. Finally, the result of the analysis shows that the total of kinds of pronunciation errors are 40 data. Misformation is the most frequent errors were made by the students. It is the highest number which 23 data out of 40 or 57,5% of the percentage. Then, omission error which 8 data out of 40 or 20%. Addition error which 8 data out of 40 or 20%. And thelast kind of error is misordering. The data is 1 out of 40 or 2,5% of the percentage. This study also found the causes of students’ error according to interlingual and intralingual transfer.